2021
DOI: 10.1016/j.ijid.2021.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Re-infection with a different SARS-CoV-2 clade and prolonged viral shedding in a hematopoietic stem cell transplantation patient

Abstract: Re-infection with different SARS-CoV-2 clade and prolonged viral shedding in a patient with hematopoietic stem cell transplantation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…In the present study, among confirmed reinfection cases with compatible symptoms in the second episode, two of them occurred as soon as 55 and 63 days (cases P9 and P16) after the first episode, but they were confirmed due to the higher number of mutations than the expected by the natural evolution of the virus. This higher number of mutations has already been observed in other cases of reinfections reported worldwide ( Alshukairi et al, 2021 ; Lee J.-S. et al, 2021 ; Selhorst et al, 2021 ; Rahman et al, 2022 ), and some reports use it as evidence of reinfection ( Sevillano et al, 2021 ; Tillett et al, 2021 ). On the other hand, cases P20 and P22 (occurring with an interval of 192 and 297 days, respectively) did not have a higher number of mutations than the expected.…”
Section: Discussionsupporting
confidence: 68%
“…In the present study, among confirmed reinfection cases with compatible symptoms in the second episode, two of them occurred as soon as 55 and 63 days (cases P9 and P16) after the first episode, but they were confirmed due to the higher number of mutations than the expected by the natural evolution of the virus. This higher number of mutations has already been observed in other cases of reinfections reported worldwide ( Alshukairi et al, 2021 ; Lee J.-S. et al, 2021 ; Selhorst et al, 2021 ; Rahman et al, 2022 ), and some reports use it as evidence of reinfection ( Sevillano et al, 2021 ; Tillett et al, 2021 ). On the other hand, cases P20 and P22 (occurring with an interval of 192 and 297 days, respectively) did not have a higher number of mutations than the expected.…”
Section: Discussionsupporting
confidence: 68%
“…Seven patients died (aged 44-92): one died of septic shock and respiratory failure [10], another one died of respiratory failure [77], and the cause of death was not reported for the remaining five patients [43,44,54,75]. Five patients were reported as still being hospitalized [38,41,61], and five patients had been discharged from hospital [35,42,52,66].…”
Section: Patient Outcomesmentioning
confidence: 99%
“…It has been also reported that the use of the anti-CD20 antibody rituximab, with or without chemotherapy, is typically associated with impaired humoral responses to influenza vaccines [38]. Similar cases are emerging with SARS-CoV-2 vaccines [39][40][41][42][43]. Rituximab is associated with B cell 141 depletion for up to 78 weeks following use.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocompromised patients likely acquire different clades of SARS-CoV-2 45 infection. Moreover, they cannot respond to the Sars-Cov-2 vaccines [ 42 , 43 ]. Alshukairi et al [ 42 ] recently described the case of a 51-year-old female patient with a history of follicular non-Hodgkin’s lymphoma and rituximab therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation